Photography on trial: the accusation of indecency Beauty and Menace/Sublime Peril - Petrillo, Concetta (Curtin University, 2020)
This exegesis contextualises and critically examines my creative practice which has children as its subject matter. It describes my prosecution under the old Censorship Act of 1996 and the Criminal Code that was in effect at the time for taking photographs of my naked and semi-naked children, which was later dismissed by a court of law. Autoethnography is used to locate the chronology and social and cultural circumstances of my practice during and after that event, and Pierre Bourdieu’s theories on habitus and field are used as a way of understanding how the socio-juridical field impacted on my creative habitus, and how my creative habitus could be enriched.